Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
Facing: Laurie Leifer, Michael Coburn, Herbert Levy, Dora Gonzales, Lloyd Gonzales; backside: Christine Watkins, Howard Watkins and Phillip Kimble